The migrant elementary teachers in the Division of City Schools, Manila a profile - Bernardino, Caridad S. 1948- (s.n.], 1973)
A sample of 154 teachers from 18 public elementary schools were involved. Migrant elementary teachers in Manila are relatively young, predominantly female, married, holders of Bachelor of Science in Elementary Education degrees, and have a few years of teaching. They migrated to Manila to join their husbands and to avail of more opportunities to pursue higher education and for cultural growth. They encounter various professional and personal problems involving pupil misbehavior, little help from parents in the solution of pupil problems, and dealing with too many supervisors. The most serious personal problem is the high cost of living in the city.